Improved Manufacturing Synthesis of Phosphorus Sulphochloride - Yang, Chunhua; Sun*, Dequn (Asian Journal of Chemistry, 2011)
A practical, improved manufacturing synthesis of phosphorus sulphochloride has been developed. The one-step process with continuous 67 times repeatable batches achieved 95 % overall isolated yield using n-tributylamine as catalyst.